Performance Evaluation of Tim Pendamping Keluarga (TPK) in theAccelerated Stunting Reduction Programme within Kutai KartanegaraRegency in 2024 - Dewi Endah Ramadhani; Ike Anggraeni G Anggraeny; Ratno Adrianto (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Stunting is a condition of impaired growth in children under five (toddlers) resulting from chronic malnutrition and recurrent infections. This condition adversely affects the development of cognitive and physical abilities. Stunting prevention necessitates a multisectoral approach, including improvement in nutrition, hygiene and sanitation, maternal and child health, and socioeconomic factors. The main challenge of controlling stunting is the complexity of its determinants, including direct factors such as inadequate nutritional intake and indirect factors such as poverty and low education (Black et al., 2013; UNICEF, 2019). Objective : The objective of this study is to assess the efficacy of Tim Pendamping Keluarga (TPK) in executing the accelerated stunting reduction program in Kutai Kartanegara Regency in 2024 Research Methods/ Implementation : a quantitative descriptive approach, utilizing monitoring data, TPK output achievements, and verification across districts and sub-districts ResultsThe analysis revealed the highest accompaniment rate for children under two at 86.84%, followed by at-risk prospective spouses at 81.45%, postpartum women at 71.62%, and the lowest for pregnant women at 25.32%. The Pearson correlation between the target numbers and those who were affected is quite strong for children under two (R=0.99), spouses (R=0.98), and postpartum women (R=0.95), and lower for pregnant women (R=0.76), indicating implementation gaps in accompaniment for pregnant women. The synergy of KRS (At-Risk Families) data collection and verification through Elsimil, together with cross-sector collaboration, contributed to a reduction in the stunting prevalence in Kutai Kartanegara (from 27.1% in 2022 to 14.3% in 2024), although increasing accompaniment coverage for pregnant women remains a priority for improvement, with Kutai Kartanegara serving as a leading example in East Kalimantan. Conclusion/Lesson Learned : Nevertheless, optimizing TPK resources remains a major concern. Accompaniment coverage for pregnant women must be strengthened in parallel with other targets, supported by TPK training or capacity building, supervision, and improvements in data integration systems so that the Kutai Kartanegara accompaniment model can be adopted as a national best practice for stunting reduction.